The Prevalence of Musculoskeletal Disorders Among Military Dentists in Metro Manila/Patricia Agnes I. Aboboto. - Aboboto, Patricia Agnes I.
Introduction Musculoskeletal disorders or MSDs are work-related health concerns prevalent globally. It affects various sectors including healthcare professionals. Among the healthcare workers, dentists are particularly susceptible to MSDs due to the nature of their work. Dentists conduct long dental procedures, assume static positions and engage in repetitive motions which largely contribute to the development of musculoskeletal disorders.